(untitled) (Research, Society and Development, 2020)
The work aimed to evaluate the microbiological quality of fresh eggs from different commercial establishments in the Metropolitan Region of São Luís, Maranhão State, Brazil. A total of 800 eggs obtained from public markets, retail supermarkets, wholesale supermarkets and grocery stores were analyzed. The samples of the internal content of the eggs were analyzed for the count of mesophilic aerobic heterotrophic bacteria (CBHAM), Staphylococcus spp., total yeasts and molds count, total and thermotolerant coliforms most probable number, and research for Salmonella spp., by conventional methods. Egg shell samples were evaluated particularly for Salmonella spp. The results for the aerobic mesophilic bacteria counts ranged from 102 to 104 CFU/mL, for Staphylococcus spp. count was 101 to 102 CFU/mL and yeast and mold count was 101 to 102 CFU/mL. The results showed that 12.5% ​​(5/40) of the samples was contaminated with total coliforms and 5% (2/40) with thermotolerant coliforms. Salmonella spp. was isolated in eggs samples, 12.5% ​​(5/40) of the internal egg and 17.5% (7/40) of the external eggs. It was concluded that fresh eggs marketed in the Metropolitan Region of São Luís presented a risk of spreading enteropathogens, regardless of the type of commercial establishment, and the commercial locations had favorable environmental conditions for microbial growth.